2016
DOI: 10.1186/s12978-016-0172-6
|View full text |Cite
|
Sign up to set email alerts
|

mHealth information for migrants: an e-health intervention for internal migrants in Vietnam

Abstract: BackgroundSocio-economic development in Vietnam has resulted in increased internal migration particularly among young women seeking employment opportunities in cities. Vietnamese female migrants who enter new environments often encounter the loss or neglect of their right to access sexual and reproductive health services. To address this, a mobile health (mHealth) intervention model was implemented over 12 months (2013–2014) in a factory in the Long Bien industrial zone of Hanoi, Vietnam.MethodsThe interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 3 publications
0
37
0
Order By: Relevance
“…After duplication removal and screening, 27 records met inclusion criteria, which were sorted into 10 initiatives (Initiative #1, 4, 6, 7, 10, 11, 13, 16, 17, and 20). Of these 27 records, there were 12 research papers [ 13 , 14 , 22 - 31 ], 8 conference presentations [ 32 - 39 ], 2 Vietnamese governmental documents [ 40 , 41 ], 2 graduate dissertations [ 42 , 43 ], 2 case studies [ 44 , 45 ], and 1 project technical report [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…After duplication removal and screening, 27 records met inclusion criteria, which were sorted into 10 initiatives (Initiative #1, 4, 6, 7, 10, 11, 13, 16, 17, and 20). Of these 27 records, there were 12 research papers [ 13 , 14 , 22 - 31 ], 8 conference presentations [ 32 - 39 ], 2 Vietnamese governmental documents [ 40 , 41 ], 2 graduate dissertations [ 42 , 43 ], 2 case studies [ 44 , 45 ], and 1 project technical report [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that more efforts are focused on delivering TB information among the migrant populations by targeting their mobile characteristics. Cellular communication in particular appears to be the most effective way to target them (Borsari et al, 2018;Rath et al, 2018;Vu et al, 2016). While the percentages calculated in the present research and in the research conducted by others (37.6% and 46.3%) may appear alarming for TB control, caution is advised, as further research is needed to assess the scale and speed of TB awareness over time.…”
Section: Discussionmentioning
confidence: 47%
“…For example, the Government of Mongolia is working with WHO to introduce mobile health at the primary health care and community levels to improve access to needed services and ensure that no one is left behind (13). In Viet Nam, a multifaceted e-health intervention providing sexual and reproductive health services to female migrants increased women's knowledge of sexual and reproductive health and improved practices related to gynaecological check-ups and use of condoms (134).…”
Section: In China the Management Plan For The Health And Family Planmentioning
confidence: 99%